Genomic anatomy of the Tyrp1 (brown) deletion complex - Smyth, Ian M. (National Academy of Sciences, 2006)
Chromosome deletions in the mouse have proven invaluable in the dissection of gene function. The brown deletion complex comprises >28 independent genome rearrangements, which have been used to identify several functional loci on chromosome 4 required for normal embryonic and postnatal development. We have constructed a 172-bacterial artificial chromosome contig that spans this 22-megabase (Mb) interval and have produced a contiguous, finished, and manually annotated sequence from these clones. The deletion complex is strikingly gene-poor, containing only 52 protein-coding genes (of which only 39 are supported by human homologues) and has several further notable genomic features, including several segments of >1 Mb, apparently devoid of a coding sequence. We have used sequence polymorphisms to finely map the deletion breakpoints and identify strong candidate genes for the known phenotypes that map to this region, including three lethal loci (l4Rn1, l4Rn2, and l4Rn3) and the fitness mutant brown-associated fitness (baf). We have also characterized misexpression of the basonuclin homologue, Bnc2, associated with the inversion-mediated coat color mutant white-based brown (B(w)). This study provides a molecular insight into the basis of several characterized mouse mutants, which will allow further dissection of this region by targeted or chemical mutagenesis.